Respuesta :
Answer:
its a formulae
we know (sinx+cosx)^3= sin^3x +cos^3x+3sinxcosx(sinx+cosx)
(a+b)^3= a^3 +b^3+3ab(a+b)
Step-by-step explanation:
(sin^2x)^3 +cos^2x)^3+3sin^2x cos^2x(sin^2x+cos^2x)
according to formulae
(sin^2x+cos^2x)^3 {as we know sin^2x+cos^2x =1}
so the (1)^3= 1
{proved}
thank u
Answer: see proof below
Step-by-step explanation:
Use the formula for factoring a cubic: (a³ + b³) = (a + b)(a² - ab + b²)
and the formula for a perfect square: a² + 2ab + b² = (a + b)²
and the Pythagorean Identity: cos²x + sin²x = 1
Proof LHS → RHS
Given: sin⁶x + cos⁶x + 3sin²x cos²x
Regroup: (sin²x)³ + (cos²x)³ + 3sin²x cos²x
Factor Cubic: (sin²x + cos²x)(sin⁴x - sin²x cos²x + cos⁴x) + 3sin²x cos²x
Pythagorean Identity: 1(sin⁴x - sin²x cos²x + cos⁴x) + 3sin²x cos²x
Add like terms: sin⁴x + 2sin²x cos²x + cos⁴x
Regroup: (sin²x)² + 2sin²x cos²x + (cos²x)²
Factor Perfect Square: (sin²x + cos²x)²
Pythagorean Identity: (1)²
Simplify: 1
LHS = RHS: 1 = 1 [tex]\checkmark\\[/tex]